Impact of Dietary-Forage-to-Concentrate Ratio on Podolian Young Bulls’ Performance and Nutritional Properties of Meat - Rosaria Marino; Mariangela Caroprese; Antonella Santillo; Agostino Sevi; Marzia Albenzio (Animals)
Animal feeding has a great impact on the management of beef farms, also affecting the nutritional properties of the meat. Therefore, in this study, the following two forage-to-concentrate ratios were tested on twenty farmed Podolian young bulls: high forage-to-concentrate (HF:C) ratio of 65:35 vs. low forage-to-concentrate (LF:C) ratio of 45:55. The fatty acid profile, bioactive compounds, α-tocopherol content, and oxidative stability were evaluated on Longissimus thoracis muscle vacuum-packaged and aged at 2 °C for 11 and 18 days, respectively. Feeding the highest forage-to-concentrate ratio improved the fatty acid profile by decreasing the saturated fatty acids (p < 0.01) and increasing the monounsaturated (p < 0.05) and n-3 polyunsaturated fatty acids (p < 0.001). In particular, the percentages of linolenic acid (C18:3n-3), eicosapentaenoic acid (EPA-C20:5n-3), DPA (C22:5n-3), and docosahexaenoic acid (DHA-C22:6n3) were significantly higher (p < 0.01) in the HF:C group than the LF:C group. The highest forage-to-concentrate ratio also increased the contents of bioactive compounds, such as creatine (p < 0.001), carnosine (p < 0.01), and anserine (p < 0.05). This study suggests that a diet composed of 65% forage may be a feasible strategy to enrich meat with healthy bioactive compounds.